Penciptaan Ruang Keempat Sebagai Basis Pembinaan Warga Gereja Pribumi Dalam Menggereja Di Jawa - Akris Mujiyono; Fibry Jati Nugroho (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2020)
The true Church must run of vocation as peacemakers. Peacemaker could do if the Church has become part of the context. If the Church were exiled by the context, it means that there are issues that must be resolved within the Church. Northen Central Java Christian Church (GKJTU), and the same with other churches on the Javanese, experienced alienation from the context. That alienation because there is the question of the identity of a Hybrid Church. To cope with it all the citizens of the Church must be built to move nearing the Javanese culture with the formation of the fourth space as its base. This fourth space is a space to interact back with the Christianity of Javanese culture that's been left behind. The fourth space is the place for contextualize. The formation of this fourth space should be seen from the poskolonial theory is Homi k. Bhabha about third space.  Gereja yang hidup dan benar harus menjalankan panggilannya sebagai pembawa damai. Pembawa damai bisa dilakukan jika Gereja telah menjadi bagian dari konteks. Jika gereja diasingkan oleh konteks itu artinya ada persoalan yang harus diselesaikan di dalam gereja itu. Gereja Kristen Jawa tengah utara (GKJTU), dan sama dengan Gereja lain di Jawa, mengalami keterasingan dari konteks. Keterasingan itu karena ada persoalan identitas Hybrid gereja. Untuk mengatasi hal itu semua warga gereja harus dibina untuk bergerak mendekati budaya Jawa dengan pembentukan ruang keempat sebagai basisnya. Ruang keempat ini adalah ruang untuk berinteraksi kembali kekristenan dengan budaya Jawa yang sudah ditinggalkannya. Pembentukan ruang keempat ini harus dilihat dari teori poskolonial Homi K. Bhabha.